Evaluation of barley for finishing swine - Robert D Goodband; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1985)
Three-hundred and ten crossbred finishing pigs averaging 110 lbs. were utilized in two growth trials to evaluate the effects of feeding barley to finishing hogs. In both experiments, there were no differences in average daily gain or average daily feed intake between hogs fed the milo-soybean meal control diet, a pelleted barley diet, or a 5% added fat barley diet. However, there was a significant decrease in average daily gain with the basal barley diet and a barley diet balanced on a lysine basis. Pelleting or adding fat significantly improved feed efficiency. In Experiment 2, hogs fed a 5% molasses diet and a rolled barley diet had the lowest average daily gains and poorest feed efficiency. These results indicate that pelleting and adding fat to barley-based diets improve average daily gain and feed efficiency. It would also appear that diets with barley substituted lb. for lb. for milo or balanced on a lysine basis have approximately 90-95% the value of a milo-soybean meal diet for finishing swine.; Swine Day, Manhattan, KS, November 21, 1985
Keywords: Swine day; 1985; Kansas Agricultural Experiment Station contribution; no. 86-145-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 486; Swine; Barley; Finishing pigs